2017
DOI: 10.1002/cta.2317
|View full text |Cite
|
Sign up to set email alerts
|

Design of a low‐power high open‐loop gain operational amplifier for capacitively‐coupled instrumentation amplifiers

Abstract: Summary We present the design of a low‐power high open‐loop gain opamp for use in chopper‐stabilized capacitively coupled instrumentation amplifiers (CCIAs). The opamp utilizes the current‐reuse folded‐cascode topology and a low‐power gain‐boosting technique to maximize its power efficiency and open‐loop gain. The proposed technique is applied to the designs of two CCIAs: the conservative CCIA with a moderate current scaling ratio and the stringent CCIA with a very high current scaling ratio. Utilizing the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Instrumentation amplifiers (IAs) are widely used in a large number of signal processing circuits. Several applications, such as clinical instrumentation, biosensor read-out circuits, electrocardiography and signal processing, etc., have been reported that pronounce the importance of IA [1][2][3][4]. In many implementations, the IA is used as an input stage to distinguish low-magnitude differential signals from unwanted high-value common-mode signals, noise, and disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumentation amplifiers (IAs) are widely used in a large number of signal processing circuits. Several applications, such as clinical instrumentation, biosensor read-out circuits, electrocardiography and signal processing, etc., have been reported that pronounce the importance of IA [1][2][3][4]. In many implementations, the IA is used as an input stage to distinguish low-magnitude differential signals from unwanted high-value common-mode signals, noise, and disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…These common principles are sometimes hidden in very specialized and specific designs, which abound for instance in the case of biosignal applications. [5][6][7] To make things even more confusing, different names are used to describe what actually is a common principle when one leaves apart the concrete implementations, which contributes to entangle the analysis and comparison of the plethora of published circuits.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although several low-voltage low power reference circuits have recently been presented in [2][3][4][5][6][7][8][9][10][11][12][13] , it is difficult to cover all of the key properties of a voltage reference, such as the temperature coefficient (TC), power supply ripple rejection (PSRR), and power and area consumptions. 1 Although several low-voltage low power reference circuits have recently been presented in [2][3][4][5][6][7][8][9][10][11][12][13] , it is difficult to cover all of the key properties of a voltage reference, such as the temperature coefficient (TC), power supply ripple rejection (PSRR), and power and area consumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, low-voltage reference generators have received much attention due to the growing interest in extremely low-power applications such as self-powered sensors. 1 Although several low-voltage low power reference circuits have recently been presented in [2][3][4][5][6][7][8][9][10][11][12][13] , it is difficult to cover all of the key properties of a voltage reference, such as the temperature coefficient (TC), power supply ripple rejection (PSRR), and power and area consumptions. For examples, the PSRR at 10 kHz frequency is only −18 dB in 2 , which is hard to meet the specifications in the system with high-frequency noises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation